2009
DOI: 10.1002/etc.30
|View full text |Cite
|
Sign up to set email alerts
|

Measuring variability in phytotoxicity testing using crop and wild plant species

Abstract: Abstract-A series of experiments was conducted to assess the level of variability in phytotoxicity testing and to investigate factors that may explain some of the observed uncertainties and inconsistencies. The work was conducted in greenhouse or growth chamber environments with plants growing individually in pots and harvested 28 d after spraying with two herbicides, glyphosate and atrazine, as formulated products. Between six and 10 doses were used on five or six replicates, necessitating over 4,500 individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 27 publications
0
32
0
Order By: Relevance
“…Therefore, if conservation of wild species is the primary intention, then ecologically relevant test species should be favoured in phytotoxicity testing, alongside the agronomically significant species for non-target crop protection. Furthermore, this experiment, and other research (Boutin et al 2004;White et al 2009;Boutin et al 2010) have demonstrated that wild species are easily workable into phytotoxicity testing protocols.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Therefore, if conservation of wild species is the primary intention, then ecologically relevant test species should be favoured in phytotoxicity testing, alongside the agronomically significant species for non-target crop protection. Furthermore, this experiment, and other research (Boutin et al 2004;White et al 2009;Boutin et al 2010) have demonstrated that wild species are easily workable into phytotoxicity testing protocols.…”
Section: Discussionmentioning
confidence: 91%
“…The reluctance to use wild species as indicators has often been attributed to difficulties in germination and cultivation. Crops are often chosen because they are considered fast growing and predictable; however, recent work has found that many wild species can be easily utilized in phytotoxicity evaluations White et al 2009;Boutin et al 2010). Comparisons of crop and wild species in terms of sensitivities to herbicides have produced mixed results.…”
Section: Introductionmentioning
confidence: 99%
“…Not only can the current population be affected, but the following generation may have reduced germination and emergence, as has been shown previously for older plants treated with glufosinate ammonium [5]. Considerable variability also exists within ecotypes of native plants and within cultivars of crops having greater than a single order of magnitude of difference in their EC25 values [27,28]. The variation changes with plant species and herbicide [27,28].…”
Section: Toxicity Changes Based On Plant Developmentmentioning
confidence: 84%
“…Considerable variability also exists within ecotypes of native plants and within cultivars of crops having greater than a single order of magnitude of difference in their EC25 values [27,28]. The variation changes with plant species and herbicide [27,28].…”
Section: Toxicity Changes Based On Plant Developmentmentioning
confidence: 98%
“…Dose–response patterns may also be different for exposures at different growth stages or for different response measures, such as seed production . Also, genetic variability will play a critical role in determining plant response to a given herbicide , and intraspecific variation among populations experiencing different environments and selections pressures is likely to be as important in determining herbicide tolerances as variation among species. We obtained seeds for our experiments from plant nurseries in Minnesota and Pennsylvania from plant lines that were raised under more controlled conditions.…”
Section: Resultsmentioning
confidence: 99%